An investigation of the effects of dithranol‐induced apoptosis in a human keratinocyte cell line. (10th January 2013) - George, Suja E.; Anderson, Rosaleen J.; Haswell, Malcolm; Groundwater, Paul W.
Abstract: Objectives: Dithranol, one of the most successful topical agents for the treatment of psoriasis, has been shown to exert its therapeutic effect by inducing keratinocyte apoptosis. To gain further insights into dithranol‐induced apoptotic events in vitro, a detailed investigation of its time‐ and dose‐dependent effects has been performed through the evaluation of selected apoptotic markers, using a human keratinocyte cell line (HaCaT) as a model. Methods: The time‐ and dose‐dependent effects of dithranol on a human keratinocyte cell line (HaCaT) were investigated through the evaluation of a series of apoptotic markers; morphological changes (electron microscopy), phosphatidylserine externalisation (flow cytometry), and caspase‐3/7 activation. Key findings: The dithranol‐induced apoptotic cascade was found to follow a well‐defined dose and time‐course, with the concentration and the period of exposure to the drug acting as the two major factors influencing the events and nature of cell death. The earliest apoptotic event detected was caspase activation (after 6 h), followed by the occurrence of phosphatidylserine externalisation (after 9 h) and subsequently the morphological characteristics associated with early and late stage apoptosis/necrosis (after 12 h). Conclusions: This study has elucidated the dose‐ and time‐response effects of dithranol‐induced apoptosis in human keratinocytes in vitro .